(adsbygoogle = window.adsbygoogle || []).push({}); [Help]The proof of (a.c)b-(a.b)c=aX(bXc)

formula: [itex]\hat{b}(\hat{a}\cdot\hat{c})-\hat{c}(\hat{a}\cdot\hat{b})=\hat{a}\times(\hat{b}\times\hat{c})[/itex]

[itex]\hat{a}\times(\hat{b}\times\hat{c})[/itex] is on the [itex]\hat{b}[/itex], [itex]\hat{c}[/itex] plane, so:

[itex]\hat{b}r+\hat{c}s=\hat{a}\times(\hat{b}\times\hat{c})[/itex]

want to proof:[itex]\begin{array}{l}r=(\hat{a}\cdot\hat{c})\\s=-(\hat{a}\cdot\hat{b})\end{array}[/itex]

[itex]\hat{a}\cdot[/itex] both sides:

[itex]\hat{a}\cdot(\hat{b}r+\hat{c}s)=\hat{a}\cdot[\hat{a}\times(\hat{b}\times\hat{c})][/itex]

[itex](\hat{a}\cdot\hat{b})r+(\hat{a}\cdot\hat{c})s=0[/itex]

It seems needing another condition to distinguish [itex]\hat{a}\times(\hat{b}\times\hat{c})[/itex] and [itex](\hat{b}\times\hat{c})\times\hat{a}[/itex]

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# [Help]The proof of (a.c)b-(a.b)c=aX(bXc)?

**Physics Forums | Science Articles, Homework Help, Discussion**